'Whatever you are, be a good one'. Issue 8 (19th October 2020) - McCarthy, Claudine
Abstract : Although Elena Sandoval‐Lucero, Ph.D., never aspired to the vice presidency, she's held the role of Vice President of the Boulder County Campus at Front Range Community College for three years now. "Whatever opportunity came my way, I worked to do my very best at that job, not with an eye on the next job but with the sincere desire to make a positive impact where I was at that moment. That led to other opportunities, and that is how I eventually became a vice president, " explained Sandoval‐Lucero, named one of NASPA's Pillars of the Profession for 2020.